TEACHING FOREIGN LANGUAGE AND LITERATURE USING MODERN TECHNOLOGY (BASED ON THE WORKS OF VIRGINIA WOOLF) - Bozorova Lobar Bazarbaevna , Khatamova Salamat Makhkamovna , Tilavoldiev Otabek Khusanbaevich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article provides and considers methods of teaching modern technologies based on the works of Virginia Woolf.